A novel 3D printed cage with microporous structure and in vivo fusion function. Issue 7 (18th March 2019) - Li, Peng; Jiang, Wei; Yan, Jia; Hu, Kun; Han, Zhenchuan; Wang, Bo; Zhao, Yongfei; Cui, Geng; Wang, Zheng; Mao, Keya; Wang, Yan; Cui, Fuzhai
Abstract: In this study, a novel 3D printed porous titanium cage (3D printed cage) with interconnected pores inside was designed and manufactured. Observations by scanning electron microscopy showed that the inside of the 3D printed cage had an octahedral porous structure, with the pores uniform in size and connected to each other. The mechanical properties analysis found that the Young's modulus and compressive strength of the porous structure were close to those of the bone structure, and the overall stiffness was slightly higher than that of the polyether ether ketone (PEEK) material, but was significantly lower than that of the titanium alloy solid module. Animal experiments indicated that the new 3D printed cage was equivalent to PEEK cage in fusion time. At 3 months, the new bone grew into the cage through the pores of the new 3D printed cage surface, which had a high bone contact rate. These results demonstrate that the 3D printed porous titanium cage has good biocompatibility and osseointegration, and has a potential clinical value as bone implants. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2019.